Late Eocene Southern Ocean cooling and invigoration of circulation preconditioned Antarctica for full-scale glaciation: - Houben, A.J.P.; Bijl, P.K.; Sluijs, A.; Schouten, S.; Brinkhuis, H. (2019)
During the Eocene‐Oligocene Transition (EOT; 34–33.5 Ma), Antarctic ice sheets relatively rapidly expanded, leading to the first continent‐scale glaciation of the Cenozoic. Declining atmospheric CO2 concentrations and associated feedbacks have been invoked as underlying mechanisms, but the role of the quasi‐coeval opening of Southern Ocean gateways (Tasman Gateway and Drake Passage) and resulting changes in ocean circulation is as yet poorly understood. Definitive field evidence from EOT sedimentary successions from the Antarctic margin and the Southern Ocean is lacking, also because the few available sequences are often incomplete and poorly dated, hampering detailed paleoceanographic and paleoclimatic analysis. Here we use organic dinoflagellate cysts (dinocysts) to date and correlate critical Southern Ocean EOT successions. We demonstrate that widespread winnowed glauconite‐rich lithological units were deposited ubiquitously and simultaneously in relatively shallow‐marine environments at various Southern Ocean localities, starting in the late Eocene (~35.7 Ma). Based on organic biomarker paleothermometry and quantitative dinocyst distribution patterns, we analyze Southern Ocean paleoceanographic change across the EOT. We obtain strong indications for invigorated surface and bottom water circulation at sites affected by polar westward‐flowing wind‐driven currents, including a westward‐flowing Antarctic Countercurrent, starting at about 35.7 Ma. The mechanism for this oceanographic invigoration remains poorly understood. The circum‐Antarctic expression of the phenomenon suggests that, rather than triggered by tectonic deepening of the Tasman Gateway, progressive pre‐EOT atmospheric cooling played an important role. At localities affected by the Antarctic Countercurrent, sea surface productivity increased and simultaneously circum‐Antarctic surface waters cooled. We surmise that combined, these processes contributed to preconditioning the Antarctic continent for glaciation.